Study of skin of an Egyptian mummy using a scanning electron microscope - Mańkowska-Pliszka, Hanna; Przychodzeń, Halina; Nawrot, Michał; Tarka, Sylwia; Wasylczyk, Piotr; Dąbkowska, Agnieszka; Fudalej, Marcin; Rzeźnicka, Ewa; Haładaj, Dagmara; Pliszka, Aleksandra (Anthropological Review, 2017)
The first study of modified human remains using an electron microscope was carried out at the end of the 1950 and in 1979 the first result of the study involving a scanning electron microscope (SEM) was published for the first time. The study was mainly focused on the structure of tissues and cells. With the help of this technique cell and tissue elements, viruses and bacterial endospores as well as the structure of epithelium and the collagen contents of dermis were identified and described. In the above-mentioned case the object of the study using a SEM was a free part of the right hand (forearm with the dorsal and palmar parts of hand) of unknown origin, with signs of mummification revealed during microscopic analysis. Our study was aimed at finding the answer to the question if the mummification of the studied limb was natural or intentional, and if the study using a SEM could link the anonymous remains with ancient Egypt.